Quantifying desertification in the Qinghai Lake Basin - Wang, Siqing; Ma, Li; Yang, Liping; Long, Xinyuan; Guan, Chao; Zhao, Changming; Chen, Ning (Frontiers in Environmental Science, 2024)
Desertification under the context of global change and intensified anthropogenic activities poses a huge challenge to sustainable development of Earth's system, including the Qinghai Lake Basin, which locates in the Tibetan Plateau. However, we know little about desertification in the Qinghai Lake Basin, which is urgent and of great importance. To that end, this study used the enhanced vegetation index (EVI) and the albedo data from MODIS satellites to explore this issue. Results based on vegetation cover (FVC), calculated from EVI, alone indicated that desertification in the Qinghai Lake Basin had reversed over last 20 years, and heavily desertified areas were concentrated along the northwestern to northern basin boundaries and on the sandy eastern shore of the Qinghai Lake. More interestingly, we found that the relationship between albedo and EVI showed a "V" shape instead of the traditional monotonic trapezoid, which might be related to multiple factors such as soil moisture, soil type, and spatial scale of sampling.This study unfolds the spatial and temporal distribution of desertification in the Qinghai Lake Basin quantitatively, and emphasizes the threshold for desertification process revealed in the EVI-Albedo feature space, which sheds light on the monitoring of desertification in alpine areas.